Level of Satisfaction and Loyalty of Mothers towards Delivery Services at Labuang Baji Hospital, Makassar - M. Askar; Dwi Sartika; Zulfikar Ali Hasan; Haerani Haerani; Muhammad Nur; Citrawati Citrawati (Humanistic Network for Science and Technology (HNST), 2019)
The 2015 MDG target for maternal mortality rate is to reduce the ratio of up to 110 maternal deaths for every 100,000 births. Until now, MMR in Indonesia is still above 305. Since 2015, the emphasis on safe labor is labor delivered by health workers in health care facilities. The purpose of this study was to analyze the relationship between the level of maternal satisfaction in each dimension of the quality of delivery services with maternal loyalty to reuse hospital facilities and recommend them to others. This analytic observational study used a cross-sectional approach. The subjects of this study were 67 mothers who used delivery services at Labuang Baji Hospital, Makassar, which were selected by simple random sampling technique. The study was conducted from October to November 2018, using a measuring instrument developed by researchers. The results showed that the dimensions of the quality of delivery services at the hospital had satisfied patients, starting from the highest level of assurance, reliability, empathy, tangible, and rensponsiveness. These five dimensions correlate significantly with loyalty to hospital reuse and the patient's willingness to recommend these facilities to others. Keywords: Service quality, Delivery services, Loyalty, Recommendations